Rekonstruksi Jihad dalam Meningkatkan Wisata Bahari di Indonesia - Wahyudi W; Sigit S; Azman A; Lomba L (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The discourse on jihad is frequently narrowed to armed violence, whereas classical and contemporary Islamic scholarship contains far broader and more contextual interpretations. This article seeks to reconstruct the concept of jihad from a qital (warfare) orientation toward mujahadah, namely earnestness and the exertion of maximum effort in productive domains of life, and to position it as an ethical framework for developing marine tourism in Indonesia. This study employs a qualitative approach through library research, examining exegetical literature, contemporary jurisprudence, and tourism policy documents to formulate a model of value integration. The findings indicate that interpreting jihad as a work ethic, ecological responsibility, and coastal community service can serve as a spiritual foundation that strengthens stakeholder commitment to marine ecosystem conservation while improving the welfare of coastal communities. This reconstruction is not intended to reduce the theological dimension of jihad but rather to broaden the scope of its actualization so that it remains relevant to sustainable development challenges. This article recommends integrating this reconstructed meaning into coastal pesantren educational curricula and community-based marine tourism policy.